COMPARATIVE ANALYSIS OF INCOME TAX 21 RATES BEFORE AND AFTER THE IMPLEMENTATION OF EFFECTIVE RATES OF PP 58/2023 ON EMPLOYEE SALARIES AT PT. UME PERSADA INDONESIA - Nur Kholidatul Aliyah; Umaimah Umaimah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to analyze the comparison of Income Tax Article 21 (PPh 21) rates before and after the implementation of the effective rates based on Government Regulation (PP) Number 58 of 2023 on employee salaries at PT Ume Persada Indonesia. The research method used is a descriptive-analytical approach with data collection techniques through interviews, document studies, and observations. The results show that the implementation of effective rates reduces the monthly tax burden on employees from January to November but increases the amount of deduction in December. Overall, the annual tax burden for employees remains unchanged significantly. This policy provides a positive impact on employees with low to medium income, but requires adjustments in the company’s administration system. This study contributes to understanding the implementation of tax policy and offers recommendations for other companies to manage tax policies more efficiently.